(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Background: Type 2 Diabetes mellitus is a multisystem disorder with oxidative stress and endothelial dysfunction. Withania somnifera Dunal (Ashwagandha) is shown to have potent antioxidant, hypoglycemic and hypolipidemic effects in several studies. The present study was planned to compare the effect of Withania somnifera on endothelial dysfunction and biomarkers in patients with diabetes mellitus. Materials and Methods: After taking IEC approval and written informed consent, 66 eligible patients, who are on metformin therapy, were randomized to receive either one capsule of highly standardized aqueous extract of Withania somnifera 250mg twice daily, one capsule of Withania somnifera 500mg twice daily or Placebo for a duration of 12 weeks. Primary efficacy parameter was a change in endothelial function (measured as change in reflection index of more than 6 %) performed by salbutamol challenge test at baseline and after 12 weeks of treatment. Secondary end points were change in biomarkers of oxidative stress (malondialdehyde, nitric oxide and glutathione), high sensitivity C-reactive protein and change in lipid profile. Safety lab parameters were measured, at baseline and after 12 weeks of treatment. Results: A total of 60 patients completed the study. Twelve weeks of treatment with Withania somnifera 250mg and 500mg produced significant reduction in reflection index (-2.52±1.32% to -7.49±3.49%) and (-2.24±1.00% to -9.03±2.42%) respectively, suggesting improvement in endothelial function versus placebo (-2.11±1.62% to -0.81±2.86%). Similarly a significant improvement in biomarkers of oxidative stress, systemic inflammation, lipid parameters and HbA1c levels, compared to baseline and placebo, was observed with Withania somnifera. All treatments are well tolerated. Conclusion: Withania somnifera showed significant improvement in endothelial function, reduction in biomarkers of oxidative stress and systemic inflammation and can be used as a therapeutic adjunctive in patients with type 2 Diabetes mellitus.